Peran Lembaga Istinbath Hukum di Indonesia dalam Menjawab Tantangan Kontemporer - Muhlis Wijaya; Romi Faslah (CV. ITTC INDONESIA, 2025)
This study examines the role of istinbath hukum (legal derivation) institutions in Indonesia in addressing contemporary challenges. It explores how these institutions adapt traditional methodologies to interpret Islamic law in response to evolving societal, technological, and global issues. The research aims to identify the challenges faced by these institutions and propose strategies for enhancing their relevance and effectiveness in a rapidly changing legal landscape. Utilizing a qualitative approach, the study analyzes the processes of legal derivation and the impact of their fatwas or rulings on public life. Findings indicate that while these institutions possess a rich heritage of legal scholarship, they often struggle with the pace of modern developments, leading to a need for more dynamic and interdisciplinary approaches to legal interpretation.